The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1111/j.1476-5381.1985.tb12914.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion dependence of the release of noradrenaline by tetraethylammonium and 4‐aminopyridine from cat splenic slices

Abstract: 1 Cat splenic slices prelabelled with [3H]-noradrenaline were incubated in oxygenated Krebsbicarbonate solution at 37°C, and the spontaneous total 3H release into different incubation media monitored. In normal Krebs bicarbonate solution, the spontaneous tritium fractional release amounted to 3.7% of the tissue radiactivity content per 5 min collection period. 2 Tetraethylammonium (TEA) increased spontaneous transmitter release in a concentrationdependent manner; the release was maximal at 30 mM and was 3.5 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, it has been previously found that in perfused cat spleen, 4-AP at high concentrations (>3 mM) induced spontaneous release of NA [8]. In cat splenic slices, the increase in spontaneous NA release induced by 4-AP (1-10 mM) was insensitive to TTX, 1 µM, both in 2.5 and 0 mM Ca 2+ solution [23].…”
Section: Discussionmentioning
confidence: 94%
“…However, it has been previously found that in perfused cat spleen, 4-AP at high concentrations (>3 mM) induced spontaneous release of NA [8]. In cat splenic slices, the increase in spontaneous NA release induced by 4-AP (1-10 mM) was insensitive to TTX, 1 µM, both in 2.5 and 0 mM Ca 2+ solution [23].…”
Section: Discussionmentioning
confidence: 94%